Cultural harmony and Religious tolerance in Islamic Spain - Osmani, Noor Mohammad (2012)
Spain came under Islamic rule in 711, when Tariq bin Ziyad, a Lieutenant of Musa bin Nusayr, Umayyad governor of Northern Africa, proceeded to punish King Roderick for his alleged crime against the teenage daughter of Julian, a Christian governor under his rule. On July 26, 711 Roderick with 90,000 men was defeated by Tariq with only 12,000 men in the Battle of Río Barbate, which marked decisive victory for the Muslims in Spain. Another report suggests that the Jews invited the Muslims to come and capture Spain, for the Christian rulers persecuted and tortured the Jews. Muslims entered Spain not as oppressors, but as liberators. In that truly multi-cultural society Jews and Christians held government positions. Jewish golden age in Spain in fact began through the Muslim rule in Spain. It was the age of freedom and tolerance for all faiths. The Jews held significant posts in all fields of government, science, medicine and literature. The most brilliant Jewish community resided therein and contributed for the development of Spain. In other places, they have been tortured and persecuted. All faiths including the Jews and Christians welcomed Muslim rule and paid regular poll tax (Jizyah) to them, as it was much less than what they paid to the previous Christian rulers. Nevertheless, it was the Jews who were the greatest beneficiaries under the Muslim rule. Throughout the human history, Al-Andalucía provided the outstanding example of tolerance and harmonious coexistence. It marks clear indication of the greatness of Islam. Nowhere else there been so long and so close of a relationship between the three Great Faiths. All Jews and Christians were allowed to maintain their beliefs and live as they desired so long as they respected and obeyed their Muslim rulers. As an immediate result of compassion and love that Islam displayed towards other faiths, many of the Jews and Christians converted to Islam without any compulsion.